Evaluation protocol for children with OSAS - Veloso-Teles, Rafaela (2013)
Introduction: Obstructive Sleep Apnea Syndrome (OSAS) in children is a distinct pathophysiological entity compared to OSAS in adults. Consequently, criteria applied in the diagnosis and treatment planning are different.Methods: Revision of the relevant medical literature, published in “Medline” in the last 10 years, related to OSAS in children in order to create a protocol with a careful anamnesis about signs and/ or symptoms of troubled breathing during sleep, other associated pathologies, important findings of upper airway obstruction in physical exam and established quality-of-life measures. A comprehensive review of the currently available diagnostic tools and treatment options was also performed.Discussion: OSAS in children remains to be an important subject for otolaryngologists because of its high prevalence, although it remains underdiagnosed and undertreated. The diagnostic and surgical criteria are still controversial and not well established.Conclusion: We prepared a protocol for OSAS in children in order to create a standardized evaluation and data collection for future studies, about the clinical aspects and complementary exams that are more relevant to the diagnosis and prognosis of this pathology.